PENGARUH LINGKUNGAN KERJA, TINGKAT PENDIDIKAN, MOTIVASI DAN KOMPENSASI TERHADAP KINERJA PEGAWAI YAYASAN IBNU UMAR CIPUTAT - Arum, Weka Arum Purnomo; Husainah, Nazifah (Universitas Sarjanawiyata Tamansiswa, 2025)
The purpose of this study was to see the influence of the work environment, Education Level, Motivation and Compensation on the performance of employees of the Ibnu Umar Ciputat Foundation. This type of research is quantitative and associative research with the respondents studied being employees who teach at the Ibnu Umar Ciputat Foundation. This study is a population study with a population of 84 respondents. The test tool in this study uses the classical assumption test. The data analysis method used is multiple regression analysis. The results of this study partially indicate that 1) the work environment does not affect employee performance, 2) Education Level has an influence on employee performance, 3) Motivation has an influence on employee performance, 4) Compensation does not affect employee performance. And simultaneously the variables Work Environment, Education Level, Motivation and Compensation together have an influence on employee performance. Keywords: Work Environment, Education Level, Motivation, Compensation, Employee Performance